Outcome of Graft Uptake and Hearing Results between ‘U’ Flap Technique and Conventional Tympanomeatal Flap Technique for Anterior and Subtotal Tympanic Membrane Perforation - Dhungana, Sundar; Rayamajhi, Pabina; Shrivastav, Rakesh Prakash (Journal of Nepal Health Research Council, 2018)
Background: Myringoplasty done for anterior and subtotal perforation needs expertise and practice than conventional underlay myringoplasty. The objective of this study was to compare the graft uptake and postoperative hearing results between ‘U’ flap and conventional tympanomeatal flap technique in anterior and subtotal tympanic membrane perforation. Methods: Sixty three patients of age fifteen years and above with chronic otitis media mucosal type with any sizedanterior and subtotal perforationof tympanic membrane were randomly allocated for myringoplasty by lottery method. There were thirty one cases in ‘U’ flap group and thirty twocases in conventional tympanomeatal flap group. Graft uptake and hearing results were assessed after six weeks and results were compared within and between the groups. Results: Graft uptake rate was 90.3%(28/31) in‘U’ flap group and it was 87.5%(28/32) in conventional tympanomeatal flap group with no statistically significant difference (p= 0.772) between the two groups. The mean pre and post-operative air bone gap in ‘U’ flap group were 23.63dB±7.77dB; 13.26dB±5.50dB and that in the conventional tympanomeatal flap group were 20.88±9.88dB, 9.42dB±6.70dB respectively. There was no statistically significant difference in hearing results between the two groups (p= 0.504). Conclusions: The graft uptake rate and hearing results of ‘U’ flap group were comparable and showed no statistically significant difference to those of conventional tympanomeatal flap group.